International students' adjustment to Philippine universities a perspective for student affairs personnel - Carullo, Olivetti A.; De Guzman, Ligaya S.; Vinluan, Lorelei R.; Manzano, Virgilio U. (2007)
This study was conducted to determine how international students construct meaning to their university experiences as they cope with the different demands of college life in a foreign university and how the student affairs services attain the institutional goals for them. The data were gathered using a face-to-face interviews with 12 undergraduate and graduate students in 3 universities in Metro Manila. Professors and Student Affairs personnel from the 3 universities also participated. It was revealed that the pre-sojourn expectations contribute to some extent to the adjustment processes of international students to their environment. There are indeed changes in their thoughts, behaviors, feelings, and perspectives in the areas of psychosocial, academic, and environmental. The results have implications on program planning of Student Affairs to internationalize higher educational institutions.
"May 2007."
Thesis (M. A. Education : Guidance)--University of the Philippines, Diliman.
Keywords: Students, Foreign -- Services -- Philippines; Students, Foreign -- Philippines -- Psychology; Students, Foreign -- Philippines -- Attitudes